EMPOWERING VILLAGE COMMUNITIES THROUGH DEVELOPING LOCAL POTENTIAL FOR CANDLECRON MANAGEMENT - Amrin, Sayful; Parera, Helena Rosalia; Ota, Maria Kristina; Ma, Stefanus Hubertus Gusti; Peni, Natalia; Nande, Marsel; Banda, Yosef Moan; Djou, Anna Maria Gadi; Ngguwa, Maria Salfin (LPPM Universitas Flores, 2025)
Community service activities in the form of providing training in making soap and candlenut oil by lecturers and students of the economic education study program were conducted in Gero village, Nagekeo district. Commodity products processed into soap and candlenut oil were utilised with the village community as partners. The geographical conditions of fertile land, supported by a community aware of the importance of using natural resources around it, allow the Gero village community to live with an adequate economy. This training assistance aims to provide breakthroughs, knowledge for innovation, and the creation of new products to the village community in making soap from candlenut oil. The soap and candlenut oil products made can become the mainstay products of Bumdes and can be used daily to save household expenses. Utilising household materials and saving expenses can also be sold to increase community income.